Karakteristik Batupasir Formasi Randangan Di Daerah Pancakarsa II Kecamatan Taluditi, Kabupaten Pohuwato - Safari, Indriani; Permana, Aang Panji; Hutagalung, Ronal (Journal of Applied Geoscience and Engineering, 2025)
The research was conducted in Pancakarsa II Village, Taluditi Subdistrict, Pohuwato Regency. The Objective of this study is to determine the distribution and characteristics of sandstone in the research area. The method employed includes surface geological mapping to identify the geological conditions of the area and comprises alluvial plain units, pyroclastic flow hill units, and denudational hill units. The stratigraphy, arranged from oldest, to youngest, consists of the Gravel Sandstone unit, the Sandstone unit, the Muddy Sandstone unit, and the Pyroclastic Breccia unit. Geological structures were analyzed using lineament analysis, revealing a predominant northeast-southwest structural orientation.the sandstone distribution in the study area shows that the Gravel Sandstone unit occupies approximately 14%, the Sandstone unit is 19%, and the Muddy Sandstone unit is 17%. Petrographic analysis based on mineral composition percentages indicates that sample ST1 is classified as Lithic Arenite, while samples ST7 and ST29 are classified as Lithic Greywacke.